Design and Stress Analysis for Spur Gears Using Solid Works Simulation - et. al., M. Ranjith Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Spur gear is the most important component which is used to transfer the power and it also transmits the motion among the machine parts between two parallel axis. The reason for causing failures in Spur gear are compressive stress, friction, bending stress, wear and tear etc. In this study the compressive stress and bending stress of a spur gear are calculated mathematically with the help of PSG DDB, and the spur gear model is simulated by using solid works software. The PSG DDB values and formulae’s are used in the mathematical calculations and then compared with solid works analysis. The final out comes are checked by comparing those results and we choose a better material for our assumed data. (PSG DDB –PSG Design Data Book)